Comparative efficacy and acceptability of treatments for restless legs syndrome in end-stage renal disease: a systematic review and network meta-analysis. Issue 9 (3rd June 2019) - Huang, Chien-Wei; Lee, Min-Jing; Wang, Liang-Jen; Lee, Po-Tsang; Tu, Yu-Kang; Hsu, Chih-Wei; Lin, Pao-Yen
Abstract: Background: Restless legs syndrome (RLS) is common in end-stage renal disease (ESRD) patients and impairs health and quality of life significantly. However, the optimal treatment of RLS in ESRD patients is uncertain and less studied compared with idiopathic RLS patients. Methods: We conducted a systematic review and network meta-analysis to compare the efficacy and acceptability of treatments for RLS in ESRD patients. Randomized controlled trials (RCTs) by February 2019 in the PubMed, Cochrane Library, Embase and ClinicalTrials.gov were reviewed. RLS severity reduction was treated as treatment efficacy, and adverse events were treated as acceptable. Both outcomes were appraised using a random effects model expressed as standardized mean differences and odds ratios with 95% confidence intervals (CIs), respectively, and were ranked using surface under the cumulative ranking curve (SUCRA) probabilities to obtain a hierarchy of interventions. Results: A total of 12 RCTs were included, comprising 9 interventions and 498 participants. All the interventions significantly improved RLS severity without critical side effects compared with placebo. Gabapentin achieved the greatest decrease of RLS severity [standardized mean difference (SMD) = 1.95, 95% CI 0.81–3.09 (SUCRA: 79.3%)], despite its frequent adverse events [SMD = 0.18, 95% CI 0.02–1.50 (19.9%)]. The combination therapy of exercise plus dopamine agonist had better efficacy [SMD = 1.60, 95% CI 0.08–3.12 (59.8%)] and acceptability [SMD = 1.41, 95% CI 0.01–142.53 (63.9%)] compared with that of vitamin C plus vitamin E [SMD = 1.50, 95% CI 0.47–2.54 (56.6%); SMD = 0.32, 95% CI 0.04–2.86 (32.5%)]. Conclusions: This network meta-analysis supports that gabapentin is the most effective treatment for RLS in ESRD patients. Exercise plus dopamine agonist is a favorable combination therapy concerning side effects. Future large RCTs with long-term treatment outcomes are necessary.